Pengaruh Pendidikan Kesehatan Olahraga terhadap Perilaku Hidup Sehat Mahasiswa Universitas PGRI Mahadewa Indonesia - Made Nohan Tara; I Made Bagia; I Gusti Ngurah Sudiarta; Komang Ayu Tri Widhiyanti (SPRINTER: Jurnal Ilmu Olahraga, 2026)
Sports health education is a crucial component in shaping healthy lifestyles among college students. This study aimed to analyze the effect of sports health education programs on healthy living behavior among students of Universitas PGRI Mahadewa Indonesia. The research design used a quasi-experimental approach with a pretest-posttest control group design. The research sample consisted of 80 third-semester students selected using purposive sampling technique, divided into an experimental group (n=40) and a control group (n=40). The research instrument was a validated healthy living behavior questionnaire with a Cronbach Alpha value of 0.87. The intervention was delivered over 12 weeks through a structured sports health education program covering physical activity, nutrition, stress management, and mental health. Data analysis employed paired t-test and independent t-test at a significance level of 0.05. The results showed a significant improvement in healthy living behavior scores in the experimental group (t=8.742; p=0.000) compared to the control group. Physical activity showed the highest improvement at 34.7%, followed by stress management (28.3%) and healthy diet (22.1%). It can be concluded that a structured sports health education program significantly improves students' healthy living behavior. The implications of this study support the integration of comprehensive sports health education into higher education curricula.